2016
DOI: 10.1182/blood-2015-07-657981
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus is effective in relapsed/refractory autoimmune cytopenias: results of a prospective multi-institutional trial

Abstract: Key Points Sirolimus monotherapy is a safe and effective steroid-sparing agent, improving autoimmune cytopenias in highly refractory patients. Sirolimus is particularly active in ALPS and should be an early therapy option for patients who require chronic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
147
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(158 citation statements)
references
References 15 publications
9
147
1
1
Order By: Relevance
“…cytopenias in PID conditions including common variable immunodeficiency and autoimmune lymphoproliferative syndrome [5,6].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…cytopenias in PID conditions including common variable immunodeficiency and autoimmune lymphoproliferative syndrome [5,6].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Interestingly, clinical studies have shown that rapamycin but not MMF treatment of patients with ALPS efficiently reduced lymphoproliferation and numbers of circulating DNT cells. [11][12][13] Although it is not clear whether rapamycin affects expansion or induces apoptosis of DNT cells or both, 14 its therapeutic efficiency suggests specific signaling requirements of DNT cells.…”
Section: Introductionmentioning
confidence: 99%
“…3 The remarkable efficacy as a second-line agent for this indication was confirmed in a recent prospective study including a further 9 ALPS-FAS patients. 4 Here, we analyze aspects of rapamycin therapy that have so far not been addressed including first-versus second-line therapy, comprehensive biomarker responses, and the consequences of stopping rapamycin by reporting our experience in 28 ALPS-FAS patients.…”
mentioning
confidence: 99%
“…activated PI3K delta syndrome 11 ), the rapamycin response in these diseases is much more variable. 4 At present, we therefore advocate first-line rapamycin only in ALPS-FAS patients. Third, we present new observations relevant for the guidance of long-term therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation